Wagons of war : a history of 10 Transport Company 1951-2011 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Defence and Strategic Studies at Massey University, Manawatu, New Zealand - Morris, Grant John (Massey University, 2012)
This thesis examines the origins, formation, operations, activities and future of 10 Transport Company. It recounts that over six decades of service, the company has continued to meet the demands placed on it to provide distribution and transport support to the New Zealand Defence Force despite a number of challenges. These range from personnel shortages, to equipment serviceability and obsolescence, ever-changing command structures and threats to its unique identity. Changes in the regional and global security environment have also historically played their part, with lessons learned and doctrine from other nations influencing and shaping activities, and experiences gained on exercises and operations by the company’s own members providing much needed training realism and validity. Now in its sixtieth year, 10 Transport Company is one of only two remaining specialist military transport providers available to the New Zealand Army, and the only one located in the North Island. Its current structure and required outputs have been driven by the changes undergone within the NZ Army over a number of years; most noticeably effects are being felt through the advent of Army Transformation, with its focus on modernisation and motorisation. The company has continued to evolve from being part of a Divisional Supply Column in a conventional war setting, to supporting infantry Brigade-sized operations in a South East Asian environmental construct, to providing task-organised elements to sustain disbursed motorised combat teams fighting in complex terrain. Acknowledging 10 Transport Company as an evolutionary entity, and within a contemporary context, this thesis then examines the relevance of the company to the New Zealand Defence Force’s anticipated future international and domestic commitments, speculating as to whether 10 Transport Company will still exist in another sixty years.
Keywords: New Zealand Defence Force; New Zealand Army; Army transportation; 10 Transport Company